2009
DOI: 10.1111/j.1365-2591.2008.01513.x
|View full text |Cite
|
Sign up to set email alerts
|

Topographical evaluation of the major apical foramen in permanent human teeth

Abstract: In this sample of teeth without apical resorption the distance between the major foramen and the anatomical root apex was always <1 mm. Deviation of the major foramen from the anatomic apex varied widely amongst tooth groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
35
2
17

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 19 publications
6
35
2
17
Order By: Relevance
“…This could be one of the causes of failure, in cases that appear radiographically well executed (Vertucci;Martos et al, 2009Martos et al, , 2010.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be one of the causes of failure, in cases that appear radiographically well executed (Vertucci;Martos et al, 2009Martos et al, , 2010.…”
Section: Discussionmentioning
confidence: 99%
“…This disadvantage is overcome by the use of a microscopic technique that allows observation under different magnifications of teeth ex vivo, either by a direct visualization of the apex, or by analyzing a sagittal or cross-sectional cut in order to visualize the entire length of the apical anatomy. This is a simple and reproducible method to study apical anatomy (Martos et al, 2009;Abarca et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…1 Morphologic analyses have shown that canals are oval-shaped or irregular in the apical third and present their largest diameter at the buccolingual aspect. 2,3,4 This concept is confirmed by the fact that the first file that clinically binds to the apex is smaller than the anatomical diameter of the apical foramen. 5 Weine 6 (1989) proposed that the apical enlargement must be three sizes larger than the first file that bound at the working length.…”
Section: Introductionmentioning
confidence: 91%
“…La mayoría de autores acotan que el foramen apical se encuentra 1 mm coronal al ápice anatómico [6][7][8] ; sin embargo, otros autores como Martos y cols. 9 plantean que esta distancia es menor a 1 mm, Marroquin y cols. 10 acotan una distancia entre 0,86 mm y 1 mm en molares inferiores y superiores; y Blaskovic y cols.…”
Section: Introductionunclassified